2021
DOI: 10.3390/geosciences11080311
|View full text |Cite
|
Sign up to set email alerts
|

Seismic and Geodetic Imaging (DInSAR) Investigation of the March 2021 Strong Earthquake Sequence in Thessaly, Central Greece

Abstract: Three strong earthquakes ruptured the northwest Thessaly area, Central Greece, on the 3, 4 and 12 March 2021. Since the area did not rupture by strong earthquakes in the instrumental period of seismicity, it is of great interest to understand the seismotectonics and source properties of these earthquakes. We combined relocated hypocenters, inversions of teleseismic P-waveforms and of InSAR data, and moment tensor solutions to produce three fault models. The first shock (Mw = 6.3) occurred in a fault segment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…The total seismic moments released by the main fault and the secondary fault are ∼3.1 × 10 18 Nm, corresponding to M W 6.3. Compared to a relatively large residual fringe revealed by a single fault model (Papadopoulos et al, 2021;Figure S11d), our two-fault model shows a noticeably better fit to the observed data with the root-mean-square (rms) of 8.5 mm (Figures 2b-2d).…”
Section: The 3 March Tyrnavos Earthquakementioning
confidence: 64%
See 2 more Smart Citations
“…The total seismic moments released by the main fault and the secondary fault are ∼3.1 × 10 18 Nm, corresponding to M W 6.3. Compared to a relatively large residual fringe revealed by a single fault model (Papadopoulos et al, 2021;Figure S11d), our two-fault model shows a noticeably better fit to the observed data with the root-mean-square (rms) of 8.5 mm (Figures 2b-2d).…”
Section: The 3 March Tyrnavos Earthquakementioning
confidence: 64%
“…The focal mechanism solutions from the National Observatory of Athens (NOA), German Research Centre for Geosciences (GFZ; https://geofon.gfz-potsdam.de/) and U.S. Geological Survey (USGS; https://www.usgs.gov/; Tables S1–S3 in Supporting Information ) indicate that the Thessaly seismic sequence composed of the aforementioned three M w > 5.5 earthquakes ruptured on a set of nearly NW‐SE‐trending gently dipping normal faults, consistent with the overall spatial distribution of aftershocks (Figure 1c). Although preliminary geodetic analysis (Ganas et al., 2021; Papadopoulos et al., 2021; Tolomei et al., 2021) highlights the activation of three buried normal faults during the Thessaly seismic sequence, De Novellis et al. (2021) proposes four unknown seismogenic faults accounting for this seismic sequence, which consist of two NE‐dipping faults responsible for Tyrnavos earthquake, one NE‐dipping fault responsible for Elassona earthquake and one SW‐dipping fault responsible for Verdikoussa earthquake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad Thiva area is characterized by normal faulting (Figure 1). It is worth noting that recent strong and destructive earthquakes in Greece have occurred on normal faults, such as the Lesvos 2017 [5,17,18], Kos 2017 [5,19,20], Samos 2020 [21][22][23][24], Thessaly 2021 [25][26][27][28][29][30], and Arkalochori (Crete) 2021 [31,32] earthquakes. Fault segmentation is common near Thiva, with the presence of a multitude of smaller normal faults all around the area.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the seismic performance of structural systems subjected to successive ground motions receives increasing attention the last years. The recent disaster held on March 2021 in Tyrnavos-Elassona region, Thessaly of Greece due to a pair of compatible magnitude (Mw=6.3, Mw=6.1) [1] shallow earthquakes with more than 1800 damaged or non-serviceable buildings, emerge the necessity of predicting the damage potential caused by mainshock-aftershock sequences in order to assess the seismic risk. It should be noted that the final, accumulated, damage includes the initial damage caused by major earthquake and the incremental damage caused by the following seismic sequence.…”
Section: Introductionmentioning
confidence: 99%